Glutathione redox cycle enzymes and selenium in severe rheumatoid arthritis: lack of antioxidative response to selenium supplementation in polymorphonuclear leucocytes. Issue 9 (September 1992) - Tarp, U; Stengaard-Pedersen, K; Hansen, J C; Thorling, E B
Abstract : The antioxidant capacity of the glutathione redox cycle and the concentrations of selenium in serum, red blood cells or whole blood, and polymorphonuclear leucocytes was evaluated in nine patients with severe rheumatoid arthritis (RA) and eight healthy controls receiving daily supplementation with 250 micrograms selenomethionine for six months. Serum and whole blood concentrations of selenium and the activity of the selenium dependent enzyme glutathione peroxidase (GSH-Px) were low in the serum, red blood cells, and polymorphonuclear leucocytes of patients with RA before selenium supplementation. During supplementation serum and whole blood concentrations of selenium and the activity of GSH-Px in serum and red blood cells of patients with RA and serum GSH-Px in controls increased. Selenium and GSH-Px in polymorphonuclear leucocytes were unaffected in patients with RA in contrast with the controls where both were augmented. Glutathione reductase activity in the red blood cells and polymorphonuclear leucocytes of patients with RA was low but increased during selenium supplementation. Whole blood concentrations of glutathione were slightly lower in patients with RA than controls and no difference in the content in polymorphonuclear leucocytes was found between the groups. The activity in red blood cells of glucose-6-phosphate dehydrogenase was high in patients with RA, indicating sufficient function of the hexose monophosphate pathway. The reduced antioxidant activity of the glutathione redox cycle in patients with severe RA was mainly due to the low availability of selenium. This was further supported by the response to selenium supplementation in serum and red blood cells. In the polymorphonuclear leucocytes, however, no biochemical effects of selenium supplementation were seen. This lack of antioxidative response could play a pathogenetic part in inflammation in patients with RA.